APPROXIMATE SOLUTIONS TO STIFF PROBLEMS OF THREE-STEP LINEAR MULTISTEP METHOD USING HERMIT POLYNOMIALS - Yelwa, Ismaila Abdullateef; Galadima, James Ibrahim; Jikantoro, Yusuf Dauda; Yakubu, Aisha A. (FUDMA JOURNAL OF SCIENCES, 2025)
Linear multistep method is a problem-solving technique mostly used to find the solution to mathematical problems involving one independent variable mostly called ordinary differential equations. However, this research seeks to carry out a formulation of an efficient numerical scheme for the approximation of first order ordinary differential equation (ODE) has been investigated. The method is a block scheme for 3-step linear multistep method using Hermit polynomials as the basis function. The continuous and discrete multi-step methods (LMM) have been formulated through the technique of collocation and interpolation. Also, numerical examples of ODE’S have been solved and results obtained show that the proposed scheme can be efficient in solving initial value problems of first order ordinary differential equations.